Evaluation of a Telehealth Training Package to Remotely Teach Caregivers to Conduct Discrete-Trial Instruction. Issue 2 (March 2023) - Higgins, William J.; Fisher, Wayne W.; Hoppe, Amanda Logan; Velasquez, Leny
The present study evaluated the effectiveness of using telehealth technologies to remotely train caregivers of children with ASD to conduct discrete-trial instruction (DTI). We used a multiple-baseline-across-participants design to evaluate caregiver correct implementation of the DTI procedures and child emission of independent correct tacts as dependent measures. We observed robust and immediate improvements for all three caregivers and two of three children. Treatment effects were maintained during follow-up and generalization probes. We discuss the benefits of telehealth technologies and other remote treatment applications.